2020
DOI: 10.21203/rs.3.rs-51600/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early results of COVID-19 pneumonia cases treated with Ultra-Low doses of Radiotherapy (ULTRA-COVID study)

Abstract: Introduction:Since the outbreak of COVID-19 pandemic, healthcare system has focused its effort to find a treatment to avoid the fatal outcome of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Benefits and risks of systemic treatments are unclear. Radiotherapy could play a role in reducing the inflammatory response in the lungs and relieve life-threatening symptomsMethods:We designed a prospective study of Ultra-Low-Doses of Therapy with Radiation Applied to COVID-19 (ULTRA-COVID) for patients th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…The findings presented support recent demonstrations of positive clinical responses to LDRT in COVID-19 pneumonia patients [6][7][8][9][10][11][12]. However, animal studies also provide support for the effectiveness of Nrf2 in protecting various tissues from pro-inflammatory challenges.…”
Section: Nrf2 Activation Protects Against Covid-19 Pneumonia Ards and Other Inflammatory Diseasessupporting
confidence: 85%
See 2 more Smart Citations
“…The findings presented support recent demonstrations of positive clinical responses to LDRT in COVID-19 pneumonia patients [6][7][8][9][10][11][12]. However, animal studies also provide support for the effectiveness of Nrf2 in protecting various tissues from pro-inflammatory challenges.…”
Section: Nrf2 Activation Protects Against Covid-19 Pneumonia Ards and Other Inflammatory Diseasessupporting
confidence: 85%
“…Sharma et al [8] reported a 90% response rate to single-fraction radiation dose of 0.7 Gy in COVID-19 patients having moderate to severe risk of disease. Similarly, Ameri et al [9,10], Moreno-Olmeado et al [11], and Sanmamed et al [12] also demonstrated beneficial outcomes in COVID-19 patients treated with LDRT.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation